Geological attractions of Mount Chamah area, Kelantan - Dony Adriansyah Nazaruddin; Hasimah Hassan; Ahmad Fadli Ahmad Sanusi (2011)
Mount Chamah (2171 m) is the highest point in Kelantan state and is one of the mountain peaks of Titiwangsa Range, the “backbone” of Peninsular Malaysia. Preliminary identification and mapping of geological attractions in Mount Chamah area have been done during the Explore Chamah 2011 program, organized by Kelantan State Forestry Department in collaboration with Universiti Malaysia Kelantan on 24 – 29 July 2011. Like other areas in the range, Mount Chamah area was also formed of granitic rocks. Several main geological attractions have been identified, such as Pichong River, Lata Pichong Waterfall, “Boat Rock” outcrop, and the morphologic panorama from the summit area.